Pakistan's tactical nuclear weapons conflict redux - Kanwal, Gurmeet; Chansoria, Monika (KW Publishers in association with Centre for Land Warfare Studies, 2014)
In paradox, the fact remains that this step has further lowered Pakistans nuclear threshold through the likely use of TNWs. The introduction of TNWs into the tactical battle area further exacerbates credibility of their control. Pakistan has not formally declared a nuclear doctrine, but it is well known that nuclear weapons are its first line of defence. The use of TNWs in the India-Pakistan case will alter the strategic scenario completely as Pakistan would threaten India with the use of TNWs in the event of New Delhi responding against Islamabad with a conventional strike in reaction to a 26/11-style terrorist attack